2010
DOI: 10.1186/1471-2164-11-s5-s11
|View full text |Cite
|
Sign up to set email alerts
|

The role of exon shuffling in shaping protein-protein interaction networks

Abstract: BackgroundPhysical protein-protein interaction (PPI) is a critical phenomenon for the function of most proteins in living organisms and a significant fraction of PPIs are the result of domain-domain interactions. Exon shuffling, intron-mediated recombination of exons from existing genes, is known to have been a major mechanism of domain shuffling in metazoans. Thus, we hypothesized that exon shuffling could have a significant influence in shaping the topology of PPI networks.ResultsWe tested our hypothesis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The first Nature paper on the draft human genome contained two figures showing "domain accretion" and "domain shuffling" in the eukaryotic evolution of transcription factors and chromatin binding proteins [21]. The sharing of domains has been an important factor in the evolution of protein interaction networks [209]. For proteins to evolve in this fashion, extended coding sequences for individual domains must be capable of both amplification (duplications) and rearrangement (cutting and splicing in new combinations).…”
Section: Protein Evolution By Amplification and Exon Shufflingmentioning
confidence: 99%
“…The first Nature paper on the draft human genome contained two figures showing "domain accretion" and "domain shuffling" in the eukaryotic evolution of transcription factors and chromatin binding proteins [21]. The sharing of domains has been an important factor in the evolution of protein interaction networks [209]. For proteins to evolve in this fashion, extended coding sequences for individual domains must be capable of both amplification (duplications) and rearrangement (cutting and splicing in new combinations).…”
Section: Protein Evolution By Amplification and Exon Shufflingmentioning
confidence: 99%
“…This issue has been explored further by a few authors more recently. First, Cancherini et al [20] hypothesized that domain shuffling would impact the topology of PPI networks. That was confirmed when they observed that the average degree (number of interactions in a node) was significantly higher in proteins with evidence of at least one domain shuffling event when compared to proteins having no detected domain shuffling events.…”
Section: Domain Shuffling Goes Systems Biologymentioning
confidence: 99%
“…those with several interacting partners, in the domain shuffling events across metazoa. This evidence led Cancherini et al [20] to conclude that domain shuffling is one of the major mechanisms in the evolution of hubs (nodes with a high degree of interactivity) in PPI networks. All these aspects are illustrated in Fig.…”
Section: Domain Shuffling Goes Systems Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multi-exon domain gain at the c-termini is due to gene fusion. Additionally, during metazoan evolution, new physical protein-protein interactions (PPIs) emerged consequent to exon shuffling of domains that mediated the interaction (3). An additional work, by Bornberg-Bauer and Mar Albà in 2013 (4), refined and expanded these mechanisms and introduced new concepts such as intrinsically disordered regions, implied links between the emergence of de-novo domains, and de-novo genes (4).…”
Section: Introductionmentioning
confidence: 99%